ANALISIS SIKAP PETANI KELAPA SAWIT TERHADAP PEDAGANG PENGUMPUL DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Agustina, Dwi Alisa; Eliza, Eliza; Khaswarina, Shorea (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research was carried out in Sungai Apit subdistrict Siak regency. In general, the society in Sungai Apit working on palm sector where in the farming and marketing farmers sell their products to the collector. The objective of this research was to analyze of palm farmers’ attitude towards merchant collector in Sungai Apit, to analyze the level of confidence and level of important palm farmers’ attribute toward of merchant collector in Sungai Apit. The method of research that used was survey method and the sample was used simple random sampling. Palm farmer was sold to merchant collector then merchant collector was sold to big merchant and after that big merchant was sold to factory. The method of analysis data was used multiatribut Fishbein attitude analysismodel, and analysis of Cartesian diagram. The results of this research showed that the attitude of farmers toward merchant collector as much as 128.77 including of good measurement category that is with the value of scale 106,99–142,64. The attributes pay cash, give a loan, keeping agreements / promises, fast service and good wassuperiority attribute and should maintainedby merchant collector. Attribute pay cash was the highest dominant attribute from the level of confidence and the level of important. Key words: Farmer, attitude, merchant collector.